Diet-related feline lower urinary tract disease in a mixed-breed angora cat: a case report - Sachio, Drevani Angelika; Suartha, I Nyoman; Arjentinia, I Putu Gede Yudhi (ARSHI Veterinary Letters, 2024)
Feline Lower Urinary Tract Disease (FLUTD) encompasses bladder and urethral disorders in cats and is influenced by factors such as diet, care, litter hygiene, and activity levels. An eight-year-old mixed-Angora queen weighing 4.1 kg presented with haematuria at the Udayana University Veterinary Teaching Hospital. Despite being active and displaying typical vital signs, the cat experienced abdominal discomfort on palpation. Diagnostic evaluations including macroscopic and microscopic urine analyses revealed haematuria, proteinuria, and struvite crystals. Radiographic and ultrasonographic examinations identified radiopaque material and uroliths in the bladder, with concurrent bladder wall thickening, although the blood parameters were normal. The cat was diagnosed with FLUTD due to urolithiasis and cystitis, and underwent dietary management, increased water intake, and daily CYSTAID Plus® supplementation. In this case, the prognosis remained positive (fausta). After 14 days, a significant improvement was noted in the absence of haematuria, and the urine appeared bright yellow without turbidity.